Effect of extract and fractions of stem bark of Morinda lucida Benth (Rubicaceae) on castor-oil induced diarrhea in mice - Ibeabuchi Jude Ali; Obiora Celestine Ugwu; Cyril Chekwube Adonu; Romanus Chijioke Omeh; Felix Kenolisa Asogwa; Ndidiamaka Hannah Okorie; Raymond Maduabuchi Okonkwo; Onyeka Obidiegwu; Patrick Chibueze Onyegbulam; Festus Basden Chiedu Okoye (African Journal of Pharmaceutical Research and Development (AJOPRED))
Morinda lucida Benth is a common Nigerian medicinal plant generally used to cure malaria parasite infection, though there is a lack of scientific reports on its capacity to treat diarrhea. The current study evaluated the effect of extract and fractions of stem bark of Morinda lucida Benth (Rubicaceae) on castor-oil-induced diarrhea in mice. The ground (500 g) was macerated in 2500 mL of methanol for 72 h, thereafter filtered and concentrated to obtain methanol extract. The extract (10 g) was subjected to gradient elution to afford different fractions. The phytochemical screening method was used to investigate the constituents of extract and fractions. The method of Lorke’s was employed in the acute toxicity study. The evaluation of anti-diarrhea activity was carried out by the castor-Oil-induced gastro-intestinal motility model. The secondary metabolites present in the extract and fractions were alkaloids, flavonoids, saponins, tannins, terpenoids, cardiac glycoside, anthraquinone glycoside, and steroids. The Acute toxicity indicated no mortality or any adverse behavioral change even at 5000 mg/kg body weight. The extract at 200 mg/kg dose gave better antidiarrheal activity than the 400 mg/kg dose indicating that the effect is not dose dependent. Among the fractions ethyl acetate at 400 mg/kg showed better activity and indicated no significant difference when compared to loperamide at 2 mg/kg dose. When compared, the antidiarrheal activity of the extract and fractions differed significantly at (p<0.05) with negative control. Morinda lucida's stem bark has an outstanding antidiarrheal effect as a result of its copious bioactive constituents.